Does Oral Implant Design Affect Marginal Bone Loss? Results of a Parallel-Group Randomized Controlled Equivalence Trial. (31st January 2018) - Spies, Benedikt C.; Bateli, Maria; Ben Rahal, Ghada; Christmann, Marin; Vach, Kirstin; Kohal, Ralf-Joachim
Abstract : Objective. To test whether or not the modified design of the test implant (intended to increase primary stability) has an equivalent effect on MBL compared to the control. Methods. Forty patients were randomly assigned to receive test or control implants to be installed in identically dimensioned bony beds. Implants were radiographically monitored at installation, at prosthetic delivery, and after one year. Treatments were considered equivalent if the 90% confidence interval (CI) for the mean difference (MD) in MBL was in between −0.25 and 0.25 mm. Additionally, several soft tissue parameters and patient-reported outcome measures (PROMs) were evaluated. Linear mixed models were fitted for each patient to assess time effects on response variables. Results. Thirty-three patients (21 males, 12 females;58.2 ± 15.2 years old) with 81 implants (47 test, 34 control) were available for analysis after a mean observation period of13.9 ± 4.5 months (3 dropouts, 3 missed appointments, and 1 missing file). The adjusted MD in MBL after one year was −0.13 mm (90% CI: −0.46–0.19; test group: −0.49; control group: −0.36;p = 0.507 ). Conclusion. Both implant systems can be considered successful after one year of observation. Concerning MBL in the presented setup, equivalence of the treatments cannot be concluded. Registration . This trial is registered with the German Clinical Trials Register (ID:DRKS00007877 ).